The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.25139/sng.v9i2.1811
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technology And The Real Estate Industry

Abstract: This paper briefly summarises the extent of the technological impact on the real estate industry, in particular,digital technology. As real estate industry is naturally characterized by several disadvantages in comparison to other industry, understanding the impact ofdigital technology is crucial to the industry on whether this technology will distrust the industry or complement the business process. The emergence of PropTech start-ups has made the industry players to re-evaluate its organisational strategy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The issue of the impact of modern technologies on the real estate industry, from various perspectives, is of interest to many researchers (Lizam, 2019;Miller, 2017;Tomal, 2020;Małkowska, 2020). The areas where modern technologies may affect individual areas of socio-economic life have had a wide impact in the context of trends that can be observed in the transformation of the traditional economy into a digital one (Kania et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The issue of the impact of modern technologies on the real estate industry, from various perspectives, is of interest to many researchers (Lizam, 2019;Miller, 2017;Tomal, 2020;Małkowska, 2020). The areas where modern technologies may affect individual areas of socio-economic life have had a wide impact in the context of trends that can be observed in the transformation of the traditional economy into a digital one (Kania et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This broad definition includes software, hardware, material, or manufacturing that is produced by small start-up companies. These start-up companies create innovation using available technology to solve limitations in the real estate industry as has been discussed in the preceding section (Lizam, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Available studies have shown that efforts were concentrated on many aspects of this issue. These included the relevance and application of ICT in estate surveying and valuation (Chiedu, 2010;Ibisola et al, 2015); factors influencing the use of ICT (Adeyemo et al, 2015;); impact of information technology on real estate income (Jud et al, 2002); application of GIS in estate management (Olaniyi et al, 2006); technology /digital disruption in real estate industry (Deloitte, 2015;Lizam, 2019;Reding et al, 2014) and PropTech evolution (Aihie, 2019;Baum, 2017;Baum et al, 2020;Olufunso, 2019;Siniak et al, 2020;Tagliaro et al, 2021). However, studies on awareness and usage of mobile technology have been limited.…”
Section: Review Of Past Studiesmentioning
confidence: 99%